“Who is Bright is Holy”: Situation of Light Designation in Akathists to Russian Saints - N. V. Semenova; Zh. Yu. Polezhaeva (Научный диалог)
The results of a study of the situation of light designation in akathists to Russian saints is presented in the article. The relevance of studying the phenomenon of light on this material is due, firstly, to the most important text-forming role of light designs in this hymnographic genre, and secondly, to the need for an in-depth study of the role of the verb in the organization of the Slavic sentence. The situation of light designation became the direct object of analysis, and the participants in this situation became the subject. The focus of research attention is on the relevant valence (semantic and syntactic) characteristics of the verb as the structural center of the sentence. The main research methods were: functional-semantic, contextual analysis of lexical units, statistical. As a result of the study, a linguistic corpus of light designations (3,157 units) was identified, their part-of-speech affiliation was characterized, a chronological distribution was demonstrated, and the dominant root-forming elements (svet-, siya-, zar-, blist-, svesh-) were established. Particular attention is paid to the grammatical mechanisms that provide light designation, as well as to its direct participants. The emphasis is on the main participant — the light. The description of the register of possible semantic roles of participants in the situation of light designation (Subject, Object and their subtypes) is focused on the division traditional in the Orthodox metaphysics of light: “uncreated light”, “smart light” and “sensual light”.